Validation of analytical and continuum numerical methods for estimating the compressive strength of masonry - Lourenço, Paulo B. (2006)
The advances in computational mechanics witnessed in the last decades have made available a large variety of numerical tools. Sophisticated non-linear models are now standard in several finite element based programs. This paper addresses the ability of continuum numerical methods, based on plasticity and cracking, as well as on analytical methods to provide reliable estimations of masonry compressive strength. In addition, a discussion on the load transfer between masonry components is presented and special attention is given to the numerical failure patterns. The results found overestimate the experimental strength and peak strain. Alternative modelling approaches that represent the micro-structure of masonry components are therefore needed.